المنظمات المتعلمة حسب بیتر سینغ ومبررات تبني التحول إلیها: دراسة حالة جامعة عمار ثلیجي من وجهة نظر عینة من أساتذة كلیة العلوم الاقتصادیة والتجاریة وعلوم التسییر - شتاتحة , عائشة (Finance and Business Economies Review, 2017)
The purpose of this study is to address the variable of the learned organization from the view-point of the thinker Peter Senge, who has made clear contributions in this field, and to try to focus on the implications of the historical development of the concept and to define the concepts related to it from the definition, characteristics, The most important justification for adopting the shift from the traditional organization concept to the concept of an educated organization was presented and the profound explanations for the necessity or inevitability of change were presented to the new concept that would ensure the organization's survival in the environment and its continuity through excellence through learning. As a society for the study and selection of a sample of the society were professors of the Faculty of Economics and Commerce and Management Sciences, and the study has reached the need for gradual transformation by committing to the application of the most important pillars of the Organization and the adoption of its characteristics. Keywords: learning organization, organizational learning, learning, leadership, horizontal structure, empowerment